Best statistic profile: an efficient parameter tuning algorithm for systematic trading methods. (2016) - Quan, Dang Minh
Selecting the right parameter's values for a systematic trading method is very important. Good parameter's values decide the trading performance of the method. In this paper, we propose an algorithm named best statistic profile to select parameter's values for systematic trading methods. The results of extensive experiments prove the efficiency and stability of the proposed mechanism.